1998
DOI: 10.3758/bf03201136
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation during the rereading of scientific texts

Abstract: Two experiments examined how cognitive resources are allocated to comprehension processes across two readings of the same scientific texts, In Experiment 1, readers read and later reread texts describing scientific topics, The results indicated that across readings, readers decreased resources allocated to proposition assembly, increased resources allocated to text-level integration, and expended a similar amount of resources to lexical access, Subjects who reread the texts after a week delay showed a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 66 publications
6
77
1
2
Order By: Relevance
“…The effect is due to perceptual fluency (repetition effects) and improvements in lexical access (Raney, 2003;Raney & Rayner, 1995). In addition, readers are more likely to execute high-level comprehension processes, such as inference generation, during rereading than during initial reading (Bourassa, Levy, Dowin, & Casey, 1998;Millis & King, 2001;Millis, Simon, & tenBroek, 1998;Raney, 1993). If low-span readers fail to use plausibility information because low-level processes, such as word recognition, are too resource consuming, then repeated reading should ease the difficulty associated with the execution of these processes.…”
Section: Resultsmentioning
confidence: 99%
“…The effect is due to perceptual fluency (repetition effects) and improvements in lexical access (Raney, 2003;Raney & Rayner, 1995). In addition, readers are more likely to execute high-level comprehension processes, such as inference generation, during rereading than during initial reading (Bourassa, Levy, Dowin, & Casey, 1998;Millis & King, 2001;Millis, Simon, & tenBroek, 1998;Raney, 1993). If low-span readers fail to use plausibility information because low-level processes, such as word recognition, are too resource consuming, then repeated reading should ease the difficulty associated with the execution of these processes.…”
Section: Resultsmentioning
confidence: 99%
“…A developmental shift toward more holistic levels of processing is also seen in resource allocation patterns with rereading. Young adult readers tend to allocate attention to process textbase features on their first encounter with text, then having established this level of representation, allocate relatively more attention to situation model features on rereading (Millis, Simon, & tenBroek, 1998;Zwaan, Magliano, & Graesser, 1995). Older readers, by contrast, appear to show relatively greater attentional allocation to situation model features (for narratives, operationalized as time allocated for low-imagery segments and for segments more important to the discourse as a whole; for expository texts, operationalized as time for low-imagery segments and spatial discontinuities) on the first reading than do younger readers (StineMorrow, Gagne, Morrow, & DeWall, 2004).…”
Section: Resource Allocation: Self-regulation As a Factor In Age Diffmentioning
confidence: 99%
“…Researchers have shown that comprehension improves across reading trials (Barnett & Seefeldt, 1989;Haenggi & Perfetti, 1992), which suggests that texts are not completely processed during the initial trial. Most relevant here, Millis, Simon, and tenBroek (1998) investigated how text processing changes across reading trials. They examined the processing resources allocated to lexical access, textbase construction, and the construction of the situation model.…”
mentioning
confidence: 99%